In Situ Hydrogel-Forming Powders Containing Eutectic Mixture of Curcumin-Arginine as a Multi-Drug Delivery System for Wound Healing Applications - Faranak Ghaderi; Saeed Fathyounes; Shahram Emami (Tabriz University of Medical Sciences, 2024)
Background: Curcumin (CUR) has antimicrobial, anti-inflammatory, and antioxidant bioactivities and is a promising molecule to treat chronic wounds. However, CUR shows limited oral bioavailability due to low aqueous solubility and dissolution, chemical instability, and rapid metabolism in the gastrointestinal tract and liver. Therefore, topical delivery seems to provide therapeutic concentrations of CUR in a controlled manner. Arginine (ARG) promotes the wound healing process. CUR and ARG form a eutectic mixture (EMCA) that can be used for simultaneous improvement of dissolution of CUR and combinational wound therapy. Here, we have formulated in situ hydrogel-forming powders of EMCA using hydrophilic carriers. Methods: EMCA was prepared by liquid-assisted grinding and analyzed by powder X-ray diffraction (PXRD) and Fourier transform infrared (FT-IR) methods. The formulations were prepared by mixing EMCA with sodium carboxy methyl cellulose, sodium alginate, and polyethylene glycol. Optical microscopy, flow property, dissolution rate, water uptake, hydrogel forming ability, release profile, and antioxidant activity of the formulated powders were measured and compared with raw CUR. Results: The solid-state analyses revealed the formation of EMCA. Photographs showed that EMCA exhibited a lower particle size than raw CUR and ARG. The formulation content significantly affected fluid uptake, hydrogel-forming ability, and dissolution rate. The optimized formulation (FEP5) showed a considerable enhancement in the dissolution rate of CUR and could control the release. FEP5 also demonstrated promising characteristics including high fluid uptake and suitable hydrogel-forming ability. FEP5 enhanced the antioxidant activity of CUR from 9% to 50%. Additionally, FEP5 exhibited improved flow properties compared to raw CUR, which is crucial for practical applications in wound therapy. Conclusion: Current work highlighted the potential of EMCA formulated as a hydrogel-forming powder as a novel formulation with improved dissolution, rapid fluid uptake, inexpensive components, feasible method of preparation, and easy application and removal for combinational wound therapy